Implementation of the Merdeka Curriculum With the Tactical Games Model To Improve Learning Outcomes of Forearm Passing Techniques Volleyball Games - Hasniah Hasniah; Jusran S; Arham Syahban; Sitti Maifa; Faisal Batennie; Hasruddin Hasruddin; Andi Nurfaidah P. (UNIVERSITAS NEGERI MAKASSAR, 2023)
This research is a classroom action research that aims to determine the level of student learning outcomes through the implementation of the Merdeka Curriculum with a Tactical Games Model to improve learning outcomes in volleyball game forearm passing technique in grade V SDS Bakau Estate students, in the 2022/2023 academic year consisting of 28 students. This research was carried out in two cycles and each cycle consisted of four stages, namely: planning, implementing, observing, and reflecting. Cycle I and cycle II carried out four meetings. Data collection on learning outcomes is done using observation sheets, students worksheets, and tests of motor skills at the end of each cycle I and the end of each cycle II. The data collected is analyzed quantitatively. From these data, the study of learning outcomes in the technique of forearm passing the volleyball game shows that students who completed their studies in cycle I were 6 people with a percentage of 21% and students who didn’t complete their studies were 22 people with a percentage of 78%. Whereas in cycle II, 21 students completed their studies with a percentage of 75% and 7 students who didn't complete their studies with a percentage of 25%. The results of the analysis also show that there is a significant increase in the learning outcomes of the passing technique in the volleyball game in grade V SDS Bakau Estate students. Based on the results of this study it can be concluded that the implementation of the Merdeka Curriculum with the tactical games model can improve student’s learning outcomes.